Pengaruh Penerapan Good Corporate Governance terhadap Kinerja Keuangan Bank Syariah - Prsojo Prasojo (Jurnal Dinamika Akuntansi dan Bisnis, 2015)
This study examine the effect the implementation of good corporate governance (GCG) to financial performance of Islamic Bank. GCG is measured using a questionnaire with a sample of employee respondents of Islamic Banks. While financial performance is easured by using financial ratios with proxied CAR, ROA,ROE, BOPO, and FDR. The study included 258 respondents who had participated to fill out a questionnaire. The number of banks that are used samples in this study were many 25 islamic banks. The financial statements are used to study was financial statements or annual report of 2013 published in there bank website. The results this study that GCG has significant positive effect on financial performance proxied with CAR, ROA, ROE, and FDR but GCG has negative significant effect on financial performance proxied with BOPO.